Effect of ultrasonic field quantity on microstructure and mechanical properties of 1060B aluminum alloy rolled plate - Aolei Fu; Ripeng Jiang; Ruiqing Li; Anqing Li; Lihua Zhang; Li Zhang (Journal of Materials Research and Technology)
The application of ultrasonic vibration during continuous casting and rolling has emerged as a promising strategy for refining the microstructure and enhancing the mechanical properties of Al alloys. This study systematically investigates the influence of the number of ultrasonic fields (0–2) on the microstructural evolution and mechanical properties of 1060B Al alloy sheets. The results demonstrate that increasing the number of ultrasonic fields significantly refines the α-Al grains and improves the mechanical properties, with the optimal effect achieved under the dual-field configuration. Under these conditions, a grain refinement rate exceeding 47 % was attained, primarily attributed to dendrite fragmentation caused by acoustic streaming and the promotion of heterogeneous nucleation. Concurrently, ultrasonic intervention induced a transition in the dominant texture from Y{111}<112> to the typical recrystallization texture R-Cube {001}<100>, while also facilitating a more uniform dispersion of nano-scale precipitates. Mechanical testing revealed that the dual-field ultrasonic treatment significantly increased the ultimate tensile strength by 27.2 % (from 78.2 MPa to 99.5 MPa) and the elongation by 29.9 % (from 37.1 % to 48.2 %), which are ascribed to an enhanced strain distribution capacity. This work elucidates the critical relationship between the number of ultrasonic fields and the resultant microstructure-property correlation, providing a scientific basis for optimizing the ultrasonic-assisted continuous casting and rolling process in industrial applications.